The effects of physical activity on self-esteem in older adults: a systematic review - Mijalković, Stefan; Stojanović, Stefan; Lilić, Ana; Ilić, Tamara; İlbak, İsmail and Kasicki, Krzysztof and Niewczas-Czarny, Patryk and Ambroży, Tadeusz and Rydzik, Łukasz (Frontiers in Public Health, 2025)
BackgroundThe aim of this systematic review was to evaluate the impact of physical activity on self-esteem levels in older adults.MethodsThis review was conducted in accordance with PRISMA 2020 guidelines. PubMed and Web of Science databases were searched using the following terms (in English): (physical activity OR physical exercise OR training) AND (self-esteem OR self-confidence OR self-respect) AND (male OR female) AND older adults.ResultsOut of 3,732 identified publications, after removing duplicates and initial screening, 17 studies were ultimately included in the analysis (total of 1,820 participants). All included studies showed a statistically significant positive relationship between regular physical activity and higher self-esteem in older adults. Particularly beneficial effects were observed for aerobic training (e.g., walking, jogging, cycling), yoga sessions, and exercises targeting strength, endurance, and coordination development.ConclusionRegular participation in activities such as walking, yoga, and moderate-intensity exercises positively influences self-esteem in older adults, making physical activity an important factor for psychological well-being in later life.Systematic review registrationThe systematic review was registered in the PROSPERO database and is available under the ID number: CRD420251011376, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251011376.